Sepsis-induced suicidal left ventricular in a patient with hypertrophic cardiomyopathy/hypertrophic obstructive cardiomyopathy - K Roshan Rao; Sarita Rao; Ankur Gupta (Apollo Medicine)
Hypertrophic cardiomyopathy is the most common heritable cardiomyopathy, manifesting as left ventricular hypertrophy. In this case, a 48-year-male patient presented with complaints of shortness of breath, uneasiness for 15 days, right lower limb pain, and one episode of fever for 2 days. He was initiated on antibiotics but gradually started developing hypotension and oliguria. After optimizing the medical therapy and as a life-saving measure, alcoholic septal ablation was done in this patient as a last resort. The patient was weaned off the ventilator after 72 h and discharged in a stable condition. He has continued follow-up for 8 months and is asymptomatic; the gradient has not recurred. The patient had both issues, and timely alcohol septal ablation helped save the patient by optimizing the hemodynamics. This is a rare situation of suicidal left ventricular induced by sepsis-induced vasodilation.